Synthesis, molecular docking and biological evaluation of 3-arylfuran-2(5H)-ones as anti-gastric ulcer agent. Issue 15 (1st August 2015) - Wang, Xu-Dong; Wei, Wei; Wang, Peng-Fei; Yi, Li-Cheng; Shi, Wei-Kang; Xie, Yong-Xiang; Wu, Lang-Zhou; Tang, Nian; Zhu, Liang-Song; Peng, Jia; Liu, Chan; Li, Xian-Hui; et al.
Graphical abstract: Abstract: 3-Arylfuran-2(5 H )-one derivatives show good antibacterial activity and were determined as tyrosyl-tRNA synthetase (TyrRS) inhibitors. In a systematic medicinal chemistry exploration, we demonstrated chemical opportunities to treat infections caused by Helicobacter pylori . Twenty 3-arylfuran-2(5 H )-ones were synthesized and evaluated for anti- H. pylori, antioxidant and anti-urease activities which are closely interconnected with H. pylori infection. The results displayed that some of the compounds show excellent antioxidant activity, and good anti- H. pylori and urease inhibitory activities. Out of these compounds, 3-(3-methylphenyl)furan-2(5 H )-one (b9 ) showed the most potent antioxidant activity (IC50 = 8.2 μM) and good anti- H. pylori activity (MIC50 = 2.6 μg/mL), and it can be used as a good candidate for discovering novel anti-gastric ulcer agent.